Effect of selenium nanoparticles on the quality and fertility of short-term preserved boar semen - Paul, Dipan Rudra; Talukdar, Dibyajyoti; Ahmed, Fazal Ali; Lalrintluanga, K.; Kalita, Girin; Tolenkhomba, T. C.; Chakravarty, Himsikha; Katiyar, Rahul; Khargharia, Gautam; Deori, Sourabh (Frontiers in Veterinary Science, 2024)
The study was carried out to investigate the effect of different concentrations of selenium nanoparticles (Se-NPs) in Beltsville Thawing Solution (BTS) extender on semen quality and fertility of Hampshire crossbred pig.For the study, semen was collected from 4 boars (10 ejaculates/boar) by gloved hand method. Each ejaculate was extended @ 1:2 with BTS extender and splitted into four aliquots. The control (C) samples were without supplementation of Se-NPs, whereas, other three were supplemented with 0.5 (T1), 1 (T2) and 2 µg ml -1 Se-NPs (T3) and stored at 15 °C in a BOD incubator. Extended semen was evaluated at 0 (immediately after dilution), 24, 48, 72 and 96 hours of storage for sperm motility, live sperm, plasma membrane integrity, acrosome integrity, DNA integrity and mitochondrial membrane potential (MMP). The mean percentage of sperm motility, live sperm and sperm with intact plasma membrane and acrosome, high MMP were significantly (P<0.01) higher in all treated groups in comparison to control at 24, 48, 72 and 96 hours of storage. Sperm with intact DNA in all treated groups was increased significantly at 48 (P<0.05) and at 72 and 96 (P<0.01) hours of storage in comparison to control group. The concentration of 1 µg ml -1 Se-NPs was found to be the best among other concentrations. In each group ten sows were artificially inseminated with the liquid semen preserved for 72 hours at 15 °C. Supplementation of 1 µg ml -1 Se-NPs yielded highest conception rate in comparison to other groups. In conclusion, supplementation of 1 µg ml -1 of Se-NPs in BTS extender resulted in best semen quality and conception rate during short time liquid preservation of boar semen.